Study on Mechanism of Rock Joint Normal Deformation Based on Mesoscopic Modified Hertzian Contact Model - Ma, Haichun; Cao, Yuan; Qian, Jiazhong; Lu, Zhitang; Li, Jianping (Rock mechanics and rock engineering, 2024)
Theoretical Hertzian contact model is used to numerically study contact area of rock joints under normal deformation, stress distribution, and spatial variation of aperture during compression. Contact points suffer from the influence of shear angle and the overlap of mutual contacts. The boundary correction contact model and tangential stress effect correction model are studied to analyze mesoscopic mechanical behavior of contact changes during joint closure. Contact area, contact force, and aperture are depicted based on modified Hertzian contact model. A single-joint loading experiments with the pressure measurement film was used to explore the local stress distribution during loading process. Experimental results are compared with numerical simulation results, and there is a good agreement between the two, which verifies the accuracy of the correction. Boundary effect of adjacent contact points truly reflects the stress distribution during joint contact closure process. The correction model is of great theoretical value for analyzing mesoscopic deformation of joints and provides a reference for actual rock mass deformation and seepage through joints. Highlights A mesoscopic contact constitutive model of rock fracture was established and its effectiveness was verified by experiments. Effective contact boundary problem in the contact process was revealed. Tangential stress effect of contact point was corrected.